2017
DOI: 10.1371/journal.pone.0182224
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic features of lymphoid follicles using blue laser imaging (BLI) endoscopy in the colorectum and its association with chronic bowel symptoms

Abstract: Background/AimIn the colorectum, lymphoid follicles hyperplasia (LH) is sometimes observed as small, round, yellowish-white nodules. The novel image-enhanced endoscopy system named blue laser imaging (BLI) provides enhanced the contrast of surface vessels using lasers for light illumination. We investigated the endoscopic features of LH observed by using BLI endoscopy and its association with chronic bowel symptoms.Patients/Methods300 participants undergoing colonoscopy for various indications were enrolled. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Moreover, the BLI has bright mode, which achieves a brighter image than usual BLI mode to maintain the enhanced contrast of surface vessels from a far field of view. It has been reported that LHs in the colonic mucosa, predominantly observed in the appendix (cecum) and the ascending colon, can be visualized more clearly by using BLI-bright mode compared to conventional white light colonoscopy [ 7 ] ( Fig 1 ). We therefore used the BLI-bright mode to evaluate the presence of LH in all cases.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the BLI has bright mode, which achieves a brighter image than usual BLI mode to maintain the enhanced contrast of surface vessels from a far field of view. It has been reported that LHs in the colonic mucosa, predominantly observed in the appendix (cecum) and the ascending colon, can be visualized more clearly by using BLI-bright mode compared to conventional white light colonoscopy [ 7 ] ( Fig 1 ). We therefore used the BLI-bright mode to evaluate the presence of LH in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous report [ 7 ], the presence of LH was defined as well demarcated white nodules. Elevated LH with erythematous change was distinguished as LH severe ( Fig 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…which are currently used clinically [10, 66, 7981]. Recent clinical studies demonstrated that Helicobacter pylori infection and eradication can induce endoscopic morphological changes and epigenetic changes in samples collected, these trends may also exist in colon [75, 82, 83]. Patient colon crypts can be isolated from the biopsies for actomyosin meshwork/4D nucelome analysis and organoids culture (Fig.…”
Section: Data Notesmentioning
confidence: 99%